Molpa: A newly recorded genus (Orthoptera: Tettigoniidae: Phaneropterinae) from China - Wu, Chao; Yang, Zhen; Liu, Chun-Xiang; Zong, Cheng (Zootaxa, 2017)
The genus Molpa Walker was previously considered to be disjunctly distributed in broad-leaf rain forests in India and Malaysia. Here we report one new species Molpa dulongensis sp. nov. from subtropic broad-leaf rain forests in southwestern Yunnan Province in China. This is a part of the Indo-Burma biodiversity hotspot area. So we can infer that Molpa is continuously distributed in broad-leaf rain forests found in Oriental Region. Redescription of the genus Molpa and description of the new species Molpa dulongensis sp. nov. are provided. The types are deposited in Insect Collection of Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).